2017
DOI: 10.1021/acs.orglett.7b01838
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Macrocyclic Organocatalysts for Kinetic Resolution of Disubstituted Epoxides with Carbon Dioxide

Abstract: Among chiral macrocycles 1 synthesized, 1m with the 3,5-bis(trifluoromethyl)phenylethynyl group was the best organocatalyst for the enantioselective synthesis of cyclic carbonates from disubstituted or monosubstituted epoxides and CO. The X-ray crystal structure of 1m revealed a well-defined chiral cavity with multiple hydrogen-bonding sites that is suitable for the enantioselective activation of epoxides. A catalytic cycle proposed was supported by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…The kinetic resolution of epoxides was employed to prepare enantioenriched epoxides [131]. Recently, Ema and co-workers reported the kinetic resolution of epoxides with CO 2 by a chiral macrocyclic organocatalyst (catalyst-1, Scheme 7) [132]. The s factor {(ln[1-c(1+ee)])/(ln[1-c(1-ee)]), where c is the conversion} is satisfactory for disubstituted epoxides (9-13), but it is low for terminal epoxides (2.5-4.1).…”
Section: Reactions Reported Inmentioning
confidence: 99%
“…The kinetic resolution of epoxides was employed to prepare enantioenriched epoxides [131]. Recently, Ema and co-workers reported the kinetic resolution of epoxides with CO 2 by a chiral macrocyclic organocatalyst (catalyst-1, Scheme 7) [132]. The s factor {(ln[1-c(1+ee)])/(ln[1-c(1-ee)]), where c is the conversion} is satisfactory for disubstituted epoxides (9-13), but it is low for terminal epoxides (2.5-4.1).…”
Section: Reactions Reported Inmentioning
confidence: 99%
“…The s ‐factors of selected substrates ( 1 b – d , 1 g ) were determined at higher conversions of around 40 % and resulted in slightly reduced s ‐factors (see Table S1 in the Supporting Information). For glycidyl ethers, our chiral‐at‐metal catalyst provided higher s ‐factors compared with most of other catalytic systems . To further evaluate the effect of the nature of the epoxide side chain on the s ‐factor, substrates 1 n – v were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Yamada et al reported that ak etoiminatocobalt(II) complex provided an s-factor of 43.5 for N,N-diphenylaminomethyloxirane, but for glycidyl phenyle ther it decreased to s = 2.2. [5b] Although av ariety of other metal (Ni, Nb, Al, Cr) complexes [8] bearing chiralS chiffbase ligands, other metal scaffolds, [9] or organocatalysts [10] were also studied in these transformations, the poor substrate Chiral-at-metal bis-cyclometalated iridium(III) complexes are introduced as an ew class of chiral catalysts for the reactiono f epoxidesw ith CO 2 to form cyclic carbonates under conditions of kinetic resolution. Reactions are typicallyp erformed at room temperature in the presence of 1mol %o fi ridium catalyst and 1.5 mol %o ft etraethylammonium bromide as the nucleophilic cocatalyst to provide selectivity factors of up to 16.6.…”
Section: Introductionmentioning
confidence: 99%
“…As the bifunctional ammonium salt catalysts C have recently demonstrated their potential for asymmetric transformations of three-membered ring heterocycles (i.e., for the kinetic resolution of oxaziridines [26]), we were interested to see if we can also achieve a kinetic resolution in the CO 2 -fixation of epoxides 1 (for selected recent examples by others see Refs. [16,[34][35][36]). We tested several epoxides 1 with different chiral catalysts C, but unfortunately in neither case any enantiomeric enrichment of the recovered starting epoxide 1 or the formed carbonate 2 could be achieved.…”
Section: Catalyst Identification Optimization Of Reaction Conditionsmentioning
confidence: 99%